Tradisi “Berzanjen” Masyarakat Banyuwangi Kajian Resepsi Sastra terhadap Teks al-Barzanji - Ashari, Hasim (MOMENTUM : Jurnal Sosial dan Keagamaan, 2018)
The text of Maulid Al-Barzanji can be considered as an Arabic religious literature. It is a very old text and is still accepted by the society, even in Banyuwangi Society, East Java, the text is very popular. Thus, it obtains a various positive feeds-back from Banyuwangi society. One of the feeds-back is, that it becomes a tradition in the society to read the text when they hold marriage ceremony, a feast for celebrating circumsion, childbirth, and celebration for celebrating the birth of our prophet Muhammad (maulid Nabi). The other feed-back is in the performing art form. Those feeds-back are a manifestation of an Arabi-Islamic cultural transformation process on Banyuwangi society East Java that brings a significant changing in the order of Banyuwangi society culture